Inco Limited's Soroako Nickel Project: A Case Study In Financing Large Overseas Mining Projects - Robert T. DeGavre (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1985)
INTRODUCTION The $645 million financing for Inco Ltd's Soroako nickel project in Indonesia not only represents a significant human achievement but also there are certain important lessons that can be derived from Inco's experience in financing the project. The paper will not present a technical assessment of the project since Inco Ltd. submitted a series of papers on this subject at the international Laterite Symposium as part of the 108th Annual Meeting of the AIME in February 1979. BRIEF HISTORY OF THE SOROAKO PROJECT Table 1 summarizes the milestones achieved in the Soroako project and its financing. Exploration Phase A contract of Work was signed on July 27, 1968 by the Republic of Indonesia and F.T. International Nickel Indonesia (P.T. Inco) covering an extensive area of over 25,000 square miles on the two southeastern arms of the island of Sulawesi. The Contract provides that P.T. Inco has the sole responsibility for financing the project and determining the terms on which the financing should be obtained, that P.T. Inco has the right to receive and hold outside of Indonesia foreign exchange revenues and to freely dispose of such revenues, and that Indonesians have the right to purchase up to 20% of the equity of P.T. Inco over a period following start of production. P.T. Inco began field investigations in the Contract Area in August 1968. Preliminary reconnaissance sampling with portable drills broadly outlined areas of favorable laterite terrain which were then systematically sampled on surveyed grids. By early 1971 sufficient exploration work had been completed to indicate that the laterite deposits near Soroako could sustain a major nickel-producing plant (figure 1). Pilot plant studies in 1970 and 1971 at Inco's research station in Port Colborne, Ontario, using two bulk samples of Soroako ore material, also confirmed that the ore could be upgraded and treated for the recovery of its metal values. Feasibility Phase Encouraged by the results of its exploration program and pilot-plant work, Inco Ltd. commissioned Toyo Engineering Company of Japan in August 1971 to prepare a capital cost estimate for a relatively small nickel project called "Stage I". Stage I was to be a single-line pyrometallurqical process plant with an annual capacity of approximately 15,000 metric tons of nickel contained in 75% nickel sulphide matte (see Figure 2). Electric power was to be supplied by a thermal power station. It is important to recognize that Inco's strategy was to develop the Soroako ore deposits in several stages: first, construct a small project to gain experience and to reduce the initial capital outlay and then later expand in one or more steps to a much larger project to achieve maximum economies. The strategy reflected both Inco's financial position in 1971 as its sales and earning dropped sharply and the difficulties previously experienced by Inco in trying to launch in the late 1960's very large "greenfield" nickel projects in New Caledonia and Guatemala. Toyo's Project Development Study was completed. in January 1972. Based upon Toyo's cost estimate for physical facilities, Inco estimated the total capital cost of Stage I to be $115 million. For the next several months, Inco ran numerous in-house financial feasibility studies, using as inputs Toyo's cost estimate and the results of its exploration and pilot plant programs. In September 1972, Inco completed a project feasibility study which was based upon a capital cost estimate of $135 million. The feasibility study was immediately made available to potential partners and lenders. Partner Negotiations The Japanese nickel market had from the outset been central to Inco's planning for the Soroako project. That market had been growing dramatically at rates in excess of 20% per annum during the 1950's and 1960's. Japan had established, for rational security and other reasons, a domestic